Oral administration of quercetin and fisetin potentiates photocarcinogenesis in UVR-exposed hairless mice - Celina Pihl; Jonatan Riber Granborg; Fernanda Endringer Pinto; Peter Bjerring; Flemming Andersen; Christian Janfelt; Merete Haedersdal; Catharina Margrethe Lerche (Elsevier, 2024)
Background: Phytochemicals have demonstrated great potential as photoprotectants. Apple-derived compounds such as quercetin, fisetin, and rutin are reported to provide topical photoprotection, but oral delivery has not been explored. Purpose: To determine the photoprotective effects of oral administration of quercetin, fisetin, and rutin, and their accumulation in skin assessed through mass spectrometry imaging. Study design: Groups of 25 hairless mice (n = 125 mice) received in the daily feed 100 mg/kg quercetin, fisetin, or rutin, 600 mg/kg nicotinamide in water as a positive control, or no supplementation as the UV control. The animals were exposed to ultraviolet radiation (UVR) equivalent to 3.5 standard erythema doses thrice weekly. Method: Mass spectroemetry imaging was used to assess local skin accumulation. Results: Oral administration of quercetin and fisetin reduced the time to tumour onset (Quercetin: second and third tumour [p < 0.045]; fisetin: third tumour [p < 0.021]), with no observed effect for rutin. Nicotinamide delayed the onset of all three recorded tumours (p < 0.0082). Results were supported by accelerated tumour growth following quercetin treatment (p < 0.0069), whereas nicotinamide reduced tumour growth (p < 0.00015). Skin accumulation of the compounds could not be demonstrated, suggesting other mechanisms must be explored to explain these effects on UVR-induced carcinogenesis. Conclusion: Oral administration of quercetin and fisetin to hairless mice increased UVR-induced tumour development. These results indicate a need for caution when selecting candidates for photoprotectants.